Treatment results of gastrointestinal perforation after endoscopic retrograde cholangiopancreatography - Miłek, Tomasz; Ciostek, Piotr; Porzycki, Piotr; Kwiatkowska, Magdalena (Gastroenterology Review/Przegląd Gastroenterologiczny, 2013)
Introduction: Duodenal perforation, damage to common bile duct or ampulla of Vater complicates from 0.7% to 10% of endoscopic retrograde cholangiopancreatography (ERCP) procedures. This complication is associated with high risk of contracting fatal diseases and death. As the endoscopic and minimally invasive treatment methods develop and gain popularity, it becomes increasingly important to determine the correct procedure in the event of gastrointestinal perforation after ERCP. Aim: To present the results of treatment of gastrointestinal perforation after ERCP and indicate the correct procedure for such cases. Material and methods : The material includes 19 patients who underwent ERCP in the years 2008–2011 and were subsequently diagnosed with duodenal perforation (except for duodenal bulb) and common bile duct (CBD). Women accounted for 68% of patients (13/19), while men constituted 32% (6/19). The mean age of patients was 66.6 years old. Indications for ERCP included cholelithiasis in 95% of cases and bile duct strictures in the remaining 5%. Treatment was conditional on the result of X-ray examination of the abdominal cavity, followed by computed tomography with aqueous contrast medium administered orally. Results: Four patients were diagnosed with intraperitoneal perforation and 15 patients with retroperitoneal perforation. In the patient group with retroperitoneal perforation the contrast media leakage (10 patients) required surgical intervention – the perforation site was located in 5 cases; in the other 5 the site could not be found. With the absence of active contrast media leakage in computed tomography (CT) (5 patients) conservative treatment was applied. Four patients with intraperitoneal perforation were referred for operative treatment. In patients under conservative treatment no complications were observed and the average hospitalization time was 9 days. Among patients with retroperitoneal perforation, who had undergone surgical treatment, complications occurred in 3 cases. The average hospitalization time in the group in which the perforation site was located was 16 days, while in the group with an unidentified perforation site it was 17 days. Patients with intraperitoneal perforation were given operative treatment, with the average hospitalization time of 12 days. Conclusions : Each patient with suspected post-ERCP perforation should undergo CT of the abdominal cavity with aqueous contrast medium administered orally. In the event of no contrast leak in patients with retroperitoneal duodenal perforation, conservative treatment should be applied. In the case of retroperitoneal perforation with active contrast media leakage outside the gastrointestinal tract, and in the case of intraperitoneal perforation, an immediate surgical intervention is recommended.